Wild boar as a reservoir of antimicrobial resistance - Torres, Rita Tinoco (2020)
Antimicrobial resistance (AMR) has been recognized as an emerging and growing problem worldwide. Knowledge concerning AMR bacteria circulating in wildlife is currently limited, although it could provide important insights into AMR emergence and persistence. Across Europe, wild boar (Sus scrofa) populations have dramatically increased their distribution and number over the last decades. In the context of AMR dynamics, wild boar is a perfect model species to unveil the emergence, spread and persistence of AMR at the human-livestock-wildlife interface. Here, we summarize the current knowledge on the importance of wild boar as a reservoir of antimicrobial resistant bacteria, and its possible use as sentinel species for surveillance. Analyses of available data showed a rising interest on this topic in the last years, highlighting the growing concern on wild boar potential role as AMR facilitator and it is foreseen that the importance of antimicrobial resistance research in wild boar will continue to increase in years to come. Available studieshave been focused on specific bacterial species, particularlyE. coli, Salmonellaspp. andEnterococcusspp., bioindicators of AMR, and have been mainly conducted in three countries: Spain, Portugal and Germany.Strikingly, AMR surveillance in wild boar is uneven and still poorly allocated as many wild boar high-density countries do not yet have publications on the topic.Overall, accumulated data showed thatwild boar are carriers of antimicrobial resistant bacteria, withvariation in the prevalence of bacterial species and thepercentage of resistance to different antibiotics. Thelack of harmonized sampling and testing protocols makes it difficult to compare AMR in wild boar.The need for the establishment of standardised protocols keen to provide quantitative comparable data is highlighted. We finally suggest the long-term monitoring of wild boar as a sentinel species for AMR surveillance in order to inform public policies on this topic.